Nerve ultrasound normal values – Readjustment of the ultrasound pattern sum score UPSS. Issue 7 (July 2018) - Grimm, Alexander; Axer, Hubertus; Heiling, Bianka; Winter, Natalie
Highlights: Normal values and upper limits are necessary for ultrasound studies. Age-, gender, height- and weight-dependency was not consistently found. Age and gender dependency were most pronounced in the larger tibial nerves of elderly men. Abstract: Objective: Reference values are crucial for nerve ultrasound. Here, we reevaluated normal nerve and fascicle cross-sectional area (CSA) values in humans and compared them to published values. Based on these data, ultrasound pattern sum score (UPSS) boundary values were revisited and readjusted. Methods: Ultrasound of different peripheral nerves was performed in 100 healthy subjects at anatomically defined landmarks. Correlations with age, gender, height and weight were calculated. Results: Overall, correspondence to other published reference values was high. Gender-dependency was found for the proximal median nerve. Dependency from height occurred in the tibial nerve (TN). Weight-dependency was not found. However, the most obvious differences were found in the TN between men >60 years and women <60 years. Thus, general boundary values were defined using the mean plus the twofold standard deviation for all subjects and nerve segments except for the TN, in which different cut-offs were proposed for elder men. Accordingly, the cut-offs for the UPSS were re-adjusted, none of the individuals revealed more than 2 points at maximum. Conclusions: The influence of distinct epidemiological factors on nerve size is most prominent in the TN, for which thus several normal values are useful. Significance: Adjusted reference values improve the accuracy of the UPSS.